Post-Elections Aceh: An Outlook for Peace and Security - Andini Gelar Ardani (2016)
With the national elections over and Partai Aceh securing an impressive win in the previously strifetorn province,, what does this mean for security in Aceh? Are there still separatist aspirations inspite of the peace accord that ended the civil war in Aceh?